The effects of an integrated training program on jump performance and knee valgus in youth football players: a randomised controlled group study - Turan, M. B.; Pekel, A.; Guler, V. S.; Kurt, M. A.; Pepe, O.; Polat, Y. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background This study aimed to examine the effects of stretching, strength, and plyometric exercise programs, implemented in addition to regular training, on jumping performance and knee valgus angles in football players.